Softness Ratio of SWIFT Gamma-Ray Bursts and Relevant Correlations - Fan Xu; Yong-Feng Huang; Liang Li; Jin-Jun Geng; Xue-Feng Wu; Song-Bo Zhang; Chen Deng; Chen-Ran Hu; Xiao-Fei Dong; Hao-Xuan Gao (The Astrophysical Journal)
The properties of X-ray flashes (XRFs) and X-ray-rich gamma-ray bursts (XRRs) as compared with classical gamma-ray bursts (C-GRBs) have been widely discussed during the SWIFT era. It has been proposed that XRFs and XRRs are low-energy extensions of the gamma-ray burst (GRB) population, and therefore, they should follow similar correlations. To further examine this idea, we collect a sample of 303 GRBs detected by SWIFT over the past two decades, all of which have reliable redshifts and spectral parameters. The bursts are classified into XRFs, XRRs, and C-GRBs based on their softness ratio (SR), which is calculated by dividing the 25–50 keV fluence with the 50–100 keV fluence. A strong correlation is found among the isotropic energy E _iso , peak luminosity L _p , and rest-frame burst duration T _90,rest , i.e., ${E}_{{\rm{iso}}}\propto {L}_{{\rm{p}}}^{0.88± 0.02}{T}_{90,{\rm{rest}}}^{0.58± 0.02}$ . Additionally, two tight three-parameter correlations involving SR and the rest-frame peak energy E _p are also derived, i.e., ${E}_{{\rm{p}}}\propto {E}_{{\rm{iso}}}^{0.20± 0.02}{{\rm{SR}}}^{-2.27± 0.15}$ and ${E}_{{\rm{p}}}\propto {L}_{{\rm{p}}}^{0.17± 0.02}{{\rm{SR}}}^{-2.33± 0.14}$ . It is interesting to note that XRFs, XRRs, and C-GRBs all follow the above correlations. The implications of these correlations and their potential application in cosmology are discussed.